2022
DOI: 10.3390/ijerph192215014
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Interlinked Frequency Dynamics of the Urban Acoustic Environment

Abstract: As sustainable metropolitan regions require more densely built-up areas, a comprehensive understanding of the urban acoustic environment (AE) is needed. However, comprehensive datasets of the urban AE and well-established research methods for the AE are scarce. Datasets of audio recordings tend to be large and require a lot of storage space as well as computationally expensive analyses. Thus, knowledge about the long-term urban AE is limited. In recent years, however, these limitations have been steadily overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…In the summer, dawn biophony is still visible in most strata but the mean amplitude difference between deep night and the dawn chorus peak reduces by 2 to 4 dB(A). Past studies in the neighboring city of Bochum identified increases in the spring normalized mean power spectrum between frequencies of 3-9kHz that subsequently reduces, supporting our findings [87]. At sport and recreation facilities, autumn acoustic environments are clearly very active from morning until night, most likely explained by the wellknown popularity of soccer in Dortmund, with practices running from morning until well in the evening under lights.…”
Section: Temporal and Seasonal Db(a) Patterns Amongst Quiet Areas And...supporting
confidence: 89%
“…In the summer, dawn biophony is still visible in most strata but the mean amplitude difference between deep night and the dawn chorus peak reduces by 2 to 4 dB(A). Past studies in the neighboring city of Bochum identified increases in the spring normalized mean power spectrum between frequencies of 3-9kHz that subsequently reduces, supporting our findings [87]. At sport and recreation facilities, autumn acoustic environments are clearly very active from morning until night, most likely explained by the wellknown popularity of soccer in Dortmund, with practices running from morning until well in the evening under lights.…”
Section: Temporal and Seasonal Db(a) Patterns Amongst Quiet Areas And...supporting
confidence: 89%
“…In the summer, dawn biophony is still visible in most strata but the mean amplitude difference between deep night and the dawn chorus peak reduces by 2 to 4 dB(A). Past studies in the neighboring city of Bochum identified increases in the spring normalized mean power spectrum between frequencies of 3-9 kHz that subsequently reduces, supporting our findings [87]. At sports and recreation facilities, autumn acoustic environments are clearly very active from morning until night, most likely explained by the well-known popularity of soccer in Dortmund, with practices running from morning until well in the evening under lights.…”
Section: Spatial Associations With Bpisupporting
confidence: 89%
“…1). In the urban acoustic environment, high correlations between frequency bins characterize the prevalence of particular sound sources and therefore provide valuable information to distinguish between the AEs of different urban settings [8]. We calculate the FCMs using Pearson correlation [7]:…”
Section: Methodsmentioning
confidence: 99%
“…FCMs, CNs and their respective ASPL were then calculated between all frequency bins for each respective day. The frequency range for all data was limited to 13 kHz, as we found no substantial power above 13 kHz in the urban environment [8].…”
Section: Datamentioning
confidence: 97%
See 1 more Smart Citation